2000
DOI: 10.1056/nejm200012283432604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotic Therapy on the Density of Vancomycin-Resistant Enterococci in the Stool of Colonized Patients

Abstract: For patients with vancomycin-resistant enterococci in stool, treatment with antianaerobic antibiotics promotes high-density colonization. Limiting the use of such agents in these patients may help decrease the spread of vancomycin-resistant enterococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
464
3
17

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 622 publications
(513 citation statements)
references
References 35 publications
(8 reference statements)
29
464
3
17
Order By: Relevance
“…22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo. A sample of VRE isolates collected from our hematologyoncology unit during our study period was found to be primarily clonal by pulsed-field gel electrophoresis analysis (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…22 On one hand, the use of anaerobic coverage (pip-tazo) has been associated with increased incidence of VRE colonization after its use, during the period of recovery of the original gut microflora. [23][24][25] On the other hand, a previous study by Bradley et al 22 found a decreased incidence of VRE while cycling ceftazidime and pip-tazo. A sample of VRE isolates collected from our hematologyoncology unit during our study period was found to be primarily clonal by pulsed-field gel electrophoresis analysis (data not shown).…”
Section: Discussionmentioning
confidence: 93%
“…23 Investigators found that anti-anaerobic antibiotics appeared to promote high-density VRE colonization that in turn was associated with a higher likelihood of VRE transmission. Thus, antibiotics used to prevent a first infection may inadvertently lead to development of a second and even more serious condition.…”
Section: Unexpected Pathogensmentioning
confidence: 99%
“…There are a large number of studies showing the impact of antibiotic use on the prevalence of VRE [19][20][21][22] . The majority of these reports show the previous use of antibiotics, e.g., vancomycin, carbapenem, metronidazole, clindamycin, and cephalosporin, as independent risk factor for the acquisition of VRE.…”
Section: Resultsmentioning
confidence: 99%